2017
DOI: 10.1590/s1806-37562016000000197
|View full text |Cite
|
Sign up to set email alerts
|

Can the six-minute walk distance predict the occurrence of acute exacerbations of COPD in patients in Brazil?

Abstract: Objective:To evaluate whether a six-minute walk distance (6MWD) of < 80% of the predicted value can predict the occurrence of acute exacerbations of COPD in patients in Brazil over a 2-year period. Methods:This was a retrospective cross-sectional study involving 50 COPD patients in Brazil. At enrollment, anthropometric data were collected and patients were assessed for pulmonary function (by spirometry) and functional exercise capacity (by the 6MWD). The patients were subsequently divided into two groups: 6MWD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Garrod et al 8 reported that patients participating in an 8-week exercise training program and receiving supplemental oxygen showed significant improvement in the 6MWD (169 ± 112 m vs. 269 ± 124 m; p = 0.001) and in Chronic Respiratory Disease Questionnaire scores (24.0 vs. 17.4; p < 0.001) when compared with those who participated in the program but did not receive supplemental oxygen 8 . The finding of a higher mean 6MWD is consistent with those of Morakami et al, 31 who compared COPD patients in Brazil and Austria and found that mean walking time and movement intensity were greater in the former than in the latter.…”
Section: Discussionsupporting
confidence: 86%
“…Garrod et al 8 reported that patients participating in an 8-week exercise training program and receiving supplemental oxygen showed significant improvement in the 6MWD (169 ± 112 m vs. 269 ± 124 m; p = 0.001) and in Chronic Respiratory Disease Questionnaire scores (24.0 vs. 17.4; p < 0.001) when compared with those who participated in the program but did not receive supplemental oxygen 8 . The finding of a higher mean 6MWD is consistent with those of Morakami et al, 31 who compared COPD patients in Brazil and Austria and found that mean walking time and movement intensity were greater in the former than in the latter.…”
Section: Discussionsupporting
confidence: 86%
“…Although fat distribution and the decline in lean mass occurred differently in patients with COPD when compared to healthy individuals, it was not global. The decrease in lower limb muscle strength, primarily in the femoral quadriceps, is more marked in patients with COPD than in healthy individuals [14,26]. In the present study, despite the worse muscle performance of individuals with severe or very severe disease, the difference was not statistically significant, as reported by Costa et al [27].…”
Section: Discussionsupporting
confidence: 49%
“…[9][10][11][12] The six-minute-walk test (6MWT) has been widely used to assess exercise capacity and predict COPD exacerbations. 10,[13][14][15] A recent systematic review suggested that, in the 6MWT, shorter walking distances indicated a high risk of severe and moderate COPD exacerbations, in which a severe exacerbation resulted in hospital admission. 10 Some studies found that a walking distance <350 m (or proxy) was an effective cut-off point for predicting exacerbations.…”
Section: Introductionmentioning
confidence: 99%